Biosensors for Seafood Safety Control—A Review - Thi Ngoc Diep Trinh; Hanh An Nguyen; Nguyen Pham Anh Thi; Nguyen Nhat Nam; Nguyen Khoi Song Tran; Kieu The Loan Trinh (Micromachines)
The increased demand for consuming seafood has made seafood production undergo a rapid period of growth. However, seafood has a high risk of contamination from harmful microorganisms and marine toxins which can cause health problems for humans consuming it. Concerning this issue, monitoring seafood safety has become a center of attention for researchers, and developing effective methods for detecting contamination in seafood has become a critical research field. In this context, biosensors have served as a promising approach to monitor seafood contamination. Compared to conventional methods, biosensors have some key benefits such as high sensitivity, selectivity, portability, and user-friendly operation. Along with significant advances in biosensors, processes of seafood monitoring can be simplified and performed outside the laboratory. In this review article, we describe the mechanisms of two main types of biosensors regarding electrochemical and optical biosensors. The current reports within the last five years on the application of these biosensors for seafood monitoring are also summarized.